Study of friction and wear behaviors of Fe-based amorphous coatings by MD simulations - Chu, Zhenhua; Zhou, Yuyun; Xu, Fa; Xu, Jingxiang; Zheng, Xingwei; Luo, Xiaotao; Shu, Yan; Zhang, Zheng; Hu, Qingsong (Frontiers in Materials, 2022)
In this study, molecular dynamics simulation is adopted to investigate the friction and wear mechanism of Fe-based amorphous composited coatings. It was found that the ceramic phase can improve plasticity of the composite coatings to reduce wear. In addition, when the Al2O3 content is 15 wt%, due to the stress concentration between ceramic phase and amorphous phase, the viscosity flow in the amorphous phase results in plastic deformation. Through this, the best wear resistance has been obtained. In addition, with the increase of compression depth, the number of atoms accumulated constantly increases, and the degree of plastic deformation becomes higher in the composite coatings. Finally, a high sliding speed results in the reduction of the wear resistance of coatings.